2001
DOI: 10.1007/s002920100480
|View full text |Cite
|
Sign up to set email alerts
|

Proliferationsrate beim kleinzelligen Bronchialkarzinom

Abstract: Immune histochemical determination of the Ki-67 protein is a useful method to estimate the prognosis of patients with small cell lung carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…There are indications, however, that a Ki-67 protein expression is an absolute requirement for progression through the cell-division cycle ( 55 ). Some studies ( 56 58 ) did not find a correlation with response after chemoradiation, similar to our results, but other studies show a correlation of the proliferation rate with the prognosis ( 59 , 60 ).…”
Section: Discussionsupporting
confidence: 90%
“…There are indications, however, that a Ki-67 protein expression is an absolute requirement for progression through the cell-division cycle ( 55 ). Some studies ( 56 58 ) did not find a correlation with response after chemoradiation, similar to our results, but other studies show a correlation of the proliferation rate with the prognosis ( 59 , 60 ).…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, only two studies to date have evaluated the association between SCLC and the Ki-67 proliferation index, one of which reported that the outcome was poor in patients with biopsy samples yielding a Ki-67 proliferation index lower than the median [12]. Another study has reported that there was no association between survival and the Ki-67 proliferation index in SCLC [13].…”
Section: Discussionmentioning
confidence: 99%
“…Plastination was invented in 1946 by Romaniak, as a technique of tissue preservation in which water and lipids from biological specimens were gradually replaced by curable polymers that then harden, leading to hard, dry, odorless display specimens that should ideally retain the original shape and color of the respective organs [14]. Romaniak utilized unpolymerized resin, and later on, Von Hagens and others used polymerizing resins to gradually replace intermediary solvents such as acetone and xylene [1,2,[15][16][17][18]. Different types of resins have been reported with different results regarding the color and volume of the final display specimens, and the main advantage of the plastination technique is that it allows for the preservation of the complete anatomical topography, and thus the morphological characteristics of the anatomical structures.…”
Section: Discussionmentioning
confidence: 99%